Optimalisasi Jaringan Wifi dan Pemanfaatan Sumber Belajar berbasis Internet untuk Pembelajaran di SMA - Kurniabudi; Abdul Rahim; Syilvia Wenny J; Ayu Ferenika; Dodi Sandra; Abdul Harris; Lola Yorita Astri; Cahyana Putra Pratama; Nida Afifah Rahma; Ferdha Nayoan; Aldrian (JPM: Jurnal Pengabdian Masyarakat, 2025)
Utilization of online learning resources is one alternative to overcome the limitations of conventional learning resources. By utilizing online learning resources, the atmosphere is more interactive and not boring. However, on the one hand, SMA Negeri 2 Batang Hari still has limitations in terms of access capacity to learning resources on the Internet. Support for adequate data communication network infrastructure is expected to overcome the problem of access to online resources. By developing a data communication network at SMA Negeri 2 Batang Hari, it can overcome obstacles in accessing learning resources and online learning for students and teachers. However, on the other hand, the knowledge and skills of students and teachers need to be improved, so that they can utilize online resources as learning resources and learning materials. The purpose of this community service activity is to optimize the use of data communication networks at SMA Negeri 2 Batang Hari by providing internet access points via a wifi network in the SMA Negeri 2 Batang Hari environment. This activity also increased the competence of students and teachers in utilizing learning resources and online learning. This activity was able to increase the capacity of internet access, especially in terms of the coverage area of ??wifi network access at SMA Negeri 2 Batang Hari which increased by 80%. In addition, this activity has increased student knowledge by 88% and teachers by 90% in utilizing learning resources and online learning.